Former welfare clients in prison: education and self-reported learning problems. - Hetland, Hilde; Iversen, Anette Christine; Eikeland, Ole Johan; Manger, Terje (European Journal of Social Work, 2015)
The aim of this study is to investigate educational background, educational wishes, actual participation in prison education, and self-reported learning problems among former child welfare clients in prison. A significant concern is that prisoners' educational level is far lower than for the general population. The same concern has also been expressed regarding former child welfare clients. The question is whether prisoners with a background from the child welfare system are especially vulnerable. The survey reported in this paper addressed the entire Norwegian prison population. We distributed a questionnaire containing questions about whether the prisoner or their family had been in contact with the welfare system, educational issues such as educational background, whether they wanted to participate in prison education and actually participated, and to what extent the participants had self-reported learning problems. We also investigated whether such learning problems affected participation in prison education. The results showed that around one-third of the 2065 respondents were former child welfare clients. The mean age of the respondents in the child welfare group was 31 years and 7.9% were women. The results further revealed that those who had been child welfare clients had a lower educational level and more self-reported learning problems than the general prison population, but most of them still wished to start an education while incarcerated.